شعر ابن الھائم المنصوري -جمع ودراسة وتحقیق- - أ.م.د.فاطمة حیدر علي (College of Education for Women, 2019)
This study comes to be as an attempt by the researcher to participate in gathering part of the heritage of the Arab nation which is dispersed between the historical and literary sources and references. The study also aims to accumulate and achieve poetry to be more useful and effective in the productions of the researchers and scholars of Arabic literature and history. The research is an extension of eight handwritings studied by the researcher for the same poet. These handwritings are found in the form of five eulogistic stanzas about the great prophet (may peace be upon him). Therefore, the researcher decides to reveal what other researchers have transcended but from the side of concern and belief in the importance of clarification or presentation.